USING ACTIVITIES IN EFL CLASSROOM - Tukhtasinova Feruzabonu Mahamatyakub qizi; Kosimova Mukammal Umaraliyevna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
This article underlines the necessity of incorporating activities at the start of an English as a Foreign Language (EFL) lesson, emphasizing how they contribute to a positive and dynamic learning environment. These activities serve a variety of functions, including grabbing students' attention, introducing new vocabulary or language structures, activating past knowledge, and fostering student rapport.